Influence of biological subject, shielding cage, and resonance frequency on radio wave propagation in a birdcage coil. Issue 10 (1st May 2016) - Seo, J.‐H.; Ryu, Y.; Han, S.‐D.; Song, H.; Kim, H.‐K.; Kim, K.‐N.
Abstract : Radio wave propagation of three types of birdcage transmit/receive radio‐frequency (RF) coils (lowpass filter, highpass filter, and bandpass filter configurations) was analysed for mouse body magnetic resonance imaging at main magnetic fields of 1.5, 3.0, 4.7, 7.0, 9.4, and 11.7 T (Larmor frequencies of 63.87, 127.74, 200, 300, 400, and 500 MHz) in terms of magnetic (| B 1 |) field sensitivity and homogeneity. The observed radio wave propagation in the central axial | B 1 | field, as influenced by the biological subject, was calculated numerically in the finite‐difference time‐domain method and compared with assessment criteria using the mean value and standard deviation. The results for different Larmor frequencies RF shielding cage configurations, and biological subject loading versus unloading were compared and are discussed in detail.